Modulation Technique Applied for THD Reduction in 3-level Flying Capacitor Multilevel Inverter - Joca, Davi R.; Barreto, Luiz H. S. C.; Oliveira Jr., Demercil S.; Henn, Gustavo A. L.; Silva, Ranoyca N. A. L. (Eletrônica de Potência, 2014)
This paper introduces a modulation technique for a three-level flying capacitor multilevel inverter applied in THD reduction. The proposed modulation improves power quality, reducing the total harmonic distortion and combining the advantages of two modulation techniques: HE-PWM and CSV-PWM. In order to validate the proposed method, the THD analysis, the loss study and the experimental results are shown concerning a three-level 6 kW 0.92 power factor flying capacitor inverter. The experimental results presented line voltage THD around 42.09% and phase voltage THD around 79.06%.